An Analysis of Moral Values through Some Characters in the Novel Lampuki by Arafat Nur - Nailur Rahmi (Department of English Education, Faculty of Teacher Training and Education, Almuslim University, 2023)
This thesis is a research on the moral values that exist in several characters and events in the novel Lampuki. This novel is one of Arafat Nur's best works. This novel is concerned with the Aceh conflict and describes in detail about war, social behavior, characters, society, and human values. Many moral messages can be learned, as well as adding insight into the appearance of Aceh's struggle at that time. Therefore, the scope of this research is focused on